2005
DOI: 10.1016/j.bbrc.2005.05.139
|View full text |Cite
|
Sign up to set email alerts
|

β-Microseminoprotein binds CRISP-3 in human seminal plasma

Abstract: Abstractβ -Microseminoprotein (MSP) and cysteine-rich secretory protein 3 (CRISP-3) are abundant constituents of human seminal plasma. Immunoprecipitation and gel filtration of seminal plasma proteins combined with examination of the proteins in their pure form showed that MSP and CRISP-3 form stable, non-covalent complexes. CRISP-3 binds MSP with very high affinity, as evidenced by surface plasmon resonance. Due to far higher abundance of MSP in prostatic fluid, it manifests large overcapacity for CRISP-3 bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…CRISP3, which is also known as specific granule protein of 28 kDa (SGP28), belongs to a family of CRISPs characterized by their size (220-230 amino acids), their secretory properties and a content of 16 highly conserved cysteine residues, which form an intra-molecular disulphide bond (27). Apart from its ability to bind A1BG in serum, Udby et al have shown that CRISP3 forms similar complexes with one of the three major proteins secreted from the prostate in seminal plasma, β-microseminoprotein (28). Human CRISP3 is also likely to be involved in the pathogenesis of prostate cancer, where CRISP3 expression is significantly upregulated (12).…”
Section: Discussionmentioning
confidence: 99%
“…CRISP3, which is also known as specific granule protein of 28 kDa (SGP28), belongs to a family of CRISPs characterized by their size (220-230 amino acids), their secretory properties and a content of 16 highly conserved cysteine residues, which form an intra-molecular disulphide bond (27). Apart from its ability to bind A1BG in serum, Udby et al have shown that CRISP3 forms similar complexes with one of the three major proteins secreted from the prostate in seminal plasma, β-microseminoprotein (28). Human CRISP3 is also likely to be involved in the pathogenesis of prostate cancer, where CRISP3 expression is significantly upregulated (12).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] We have previously reported that the cysteine-rich secretory family (CRISP) family member CRISP3 also forms a high-affinity complex with MSMB in human seminal plasma. 20 CRISP3 has been found to be one of the most upregulated genes in prostate cancer compared to benign tissue, 21,22 and was proposed to be a useful biomarker for prostate cancer. 23,24 Recently we reported that in a tissue microarray (TMA) with samples from 945 prostate cancer patients undergoing radical prostatectomy (RP), high CRISP3 and low MSMB expression were associated with poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] In contrast with MSMB, CRISP3 (also known as specific granule protein of 28 kDa (SGP28)) levels are low in normal and benign prostatic tissue and seminal plasma, but often increased in prostate cancer, [26][27][28] in turn rendering the proposition that increasing levels of CRISP3 may be a biomarker for prostate cancer. 29 Interestingly, CRISP3 will readily form a complex with MSMB in the seminal plasma, 30 and it has been speculated that this binding may hinder any putative MSMB action. However, to date very little is known about the functions of both MSMB, CRISP3, and the complex they form.…”
mentioning
confidence: 99%